Mitochondrial DNA hyperdiversity and its potential causes in the marine periwinkle Melarhaphe neritoides (Mollusca: Gastropoda) - Fourdrilis,Séverine; Mardulyn,Patrick; Hardy,Olivier J.; Jordaens,Kurt; de Frias Martins,António Manuel; Backeljau,Thierry (PeerJ, 2016)
We report the presence of mitochondrial DNA (mtDNA) hyperdiversity in the marine periwinkle Melarhaphe neritoides (Linnaeus, 1758), the first such case among marine gastropods. Our dataset consisted of concatenated 16S-COI-Cytb gene fragments. We used Bayesian analyses to investigate three putative causes underlying genetic variation, and estimated the mtDNA mutation rate, possible signatures of selection and the effective population size of the species in the Azores archipelago. The mtDNA hyperdiversity in M. neritoides is characterized by extremely high haplotype diversity (Hd = 0.999 ± 0.001), high nucleotide diversity (π = 0.013 ± 0.001), and neutral nucleotide diversity above the threshold of 5% (πsyn = 0.0677). Haplotype richness is very high even at spatial scales as small as 100m2. Yet, mtDNA hyperdiversity does not affect the ability of DNA barcoding to identify M. neritoides. The mtDNA hyperdiversity in M. neritoides is best explained by the remarkably high mutation rate at the COI locus (μ = 5.82 × 10−5 per site per year or μ = 1.99 × 10−4 mutations per nucleotide site per generation), whereas the effective population size of this planktonic-dispersing species is surprisingly small (Ne = 5, 256; CI = 1,312–3,7495) probably due to the putative influence of selection. Comparison with COI nucleotide diversity values in other organisms suggests that mtDNA hyperdiversity may be more frequently linked to high μ values and that mtDNA hyperdiversity may be more common across other phyla than currently appreciated.
Keywords: mtDNA hyperdiversity; Haplotype diversity; Nucleotide diversity; Planktonic dispersal; Effective population size; Selection; Mutation rate